The Structure of Consumption Expenditure And Economic Activity in The Wielkopolska Region - Monika KAPLER (Communications of International Proceedings, 2022)
The article deals with the analysis of consumption expenditure and its impact on economic activity in Poland. Consumer behavior in the marketplace is an integral part of any economy. The level, dynamics of development and the structure of consumption expenditures are conditioned by many factors at the macro level, such as the economy and society, and at the micro level, i.e. in households. They can, especially at the level of the individual - household, indicate the level of development of the economy and society, as well as about global development.The first part of the article presents some theoretical aspects of consumption and the factors shaping it. The second part is a subject analysis of consumption based on the level and structure of household expenditure in Poland in 2013-2020 in the context of socio-economic development, with the specification of the Wielkopolska region. The author focused on this region due to its role in the country's economy. For many years, Wielkopolska has been one of the most economically developed regions in Poland. Apart from a highly developed and diversified industrial sector, the region is characterized by effective and efficient agriculture and a highly developed service sector, especially financial and advisory. The final part consists of conclusions and a summary. The main source of data concerning the preparation of the article were reports published by the Central Statistical Office. The results of the analyzes show that in the Wielkopolska region there were real economic development processes. However, these processes were accompanied by persistent disproportions in the standard of social life.
Keywords: consumer spending; economic development; consumer; regional development